The Race for Sustainable Development - Yeow, Daniel (Consilience, 2008)
The world has changed a great deal in recent times and the challenges which present themselves are unlike any that we have faced before. Foremost among these are climate change, world poverty, and the many forces which are inextricably linked to these such as population growth, economic development, and the spread of technology. In this article, the convergence of these pressures is examined in light of the challenges and opportunities offered by globalization. The role of information will be examined with the view to shedding new perspective on some of the more pervasive problems that accompany globalization and economic growth.